Volatile oil composition, phytochemical screening and larvicidal activities of indigofera tinctoria L. against African Sesamia calamistis - Mohammed, I.; Olaoluwa, O.O.; Alabi, O.Y.; Banwo, O.M.; Ayodele, M.A.; Flamini, G. (2025)
Sesamia calamistis, or the African pink stem borer, is a common pest in Nigeria that affects important crops like maize. Conventional pest control has relied heavily on synthetic insecticides, which pose risks due to their toxicity to mammals and potential ecological harm. Consequently, there is increasing interest in alternative pest management strategies utilising plant extracts. Hence, the aim of this research was to examine the volatile oil constituents, phytochemical components of Indigofera tinctoria, and evaluate its larvicidal effectiveness against S. calamistis. Phytochemical screening was performed using established methods, and volatile oils were extracted via hydrodistillation and characterized using gas chromatography-mass spectrometry (GC–MS). The larvicidal activity of the extracts was tested using the feeding assay method. The GC–MS analysis revealed that I. tinctoria leaf oils contained twenty compounds, while seed oils had eleven, accounting for 95.7% and 99.5% of the total oil, respectively. Phytol (34.1%) and 1-octen-3-ol (63.8%) were the major constituents in the leaf and seed oil of I. tinctoria, respectively. Flavonoids, alkaloids, and cardiac glycosides were present in the hexane, ethyl acetate, and ethanol fractions. Notably, the ethyl acetate fraction exhibited the highest larval mortality rate of 70.0% at a 0.4% concentration. These bioactive compounds found in I. tinctoria might be responsible for the larvicidal effects observed against S. calamistis in maize and the ethyl acetate fraction is therefore recommended for further isolation to ascertain the compound responsible for the larvicidal activities.